Técnicas de retención de personal (2019)
The objective of the present investigation is to do a bibliographic review of the theme personal retention since the first author talk about this theme until the present days. When we have clearer this theme and more information, we proceed to see and analyze this theme in the organization Autopista 140, comparing the retention they have established with the biggest organization and doing recommendations, so they can improve de personal retention and being a better organization with the best human capital.